Spatial distribution of selenium-mercury in Arctic seabirds - Marta Cruz-Flores; Jérémy Lemaire; Maud Brault-Favrou; Signe Christensen-Dalsgaard; Carine Churlaud; Sébastien Descamps; Kyle Elliott; Kjell Einar Erikstad; Alexey Ezhov; Maria Gavrilo; David Grémillet; Gaël Guillou; et al. (Environmental Pollution, 2024)

Meeting Paris agreement objectives will temper seabird winter distribution shifts in the North Atlantic Ocean - Manon Clairbaux; William W. L. Cheung; Paul Mathewson; Warren Porter; Nicolas Courbin; Jérôme Fort; Hallvard Strøm; Børge Moe; Per Fauchald; Sebastien Descamps; Hálfdán Helgason; Vegard S. Bråthen; et al. (Global Change Biology, 2021)
We explored the implications of reaching the Paris Agreement Objective of limiting global warming to Alle alle , Fratercula arctica , Uria aalge , Uria lomvia and Rissa tridactyla ) using tracking data for ~1500 individuals through resource selection functions based on mechanistic modeling of seabird energy requirements, and a dynamic bioclimate envelope model of seabird prey. Future winter distributions were predicted to shift with climate change, especially when global warming exceed 2°C under a “no mitigation” scenario, modifying seabird wintering hotspots in the North Atlantic Ocean. Our findings suggest that meeting Paris agreement objectives will limit changes in seabird selected habitat location and size in the North Atlantic Ocean during the 21st century. We thereby provide key information for the design of adaptive marine‐protected areas in a changing ocean.

Inferring seabird activity budgets from leg-mounted time–depth recorders - Jannie Fries Linnebjerg; Nicholas Per Huffeldt; Knud Falk; Flemming R. Merkel; Anders Mosbech; Morten Frederiksen (Journal of Ornithology, 2014)